NGS Transcriptomes and Enzyme Inhibitors Unravel Complexity of Picrosides Biosynthesis in Picrorhiza kurroa Royle ex. Benth. - Kirti Shitiz; Neha Sharma; Tarun Pal; Hemant Sood; Rajinder S Chauhan (PLoS ONE, 2015)
Picrorhiza kurroa is an important medicinal herb valued for iridoid glycosides, Picroside-I (P-I) and Picroside-II (P-II), which have several pharmacological activities. Genetic interventions for developing a picroside production platform would require knowledge on biosynthetic pathway and key control points, which does not exist as of today. The current study reports that geranyl pyrophosphate (GPP) moiety is mainly contributed by the non-mevalonate (MEP) route, which is further modified to P-I and P-II through phenylpropanoid and iridoid pathways, in total consisting of 41 and 35 enzymatic steps, respectively. The role of the MEP pathway was ascertained through enzyme inhibitors fosmidomycin and mevinolin along with importance of other integrating pathways using glyphosate, aminooxy acetic acid (AOA) and actinomycin D, which overall resulted in 17%-92% inhibition of P-I accumulation. Retrieval of gene sequences for enzymatic steps from NGS transcriptomes and their expression analysis vis-à-vis picrosides content in different tissues/organs showed elevated transcripts for twenty genes, which were further shortlisted to seven key genes, ISPD, DXPS, ISPE, PMK, 2HFD, EPSPS and SK, on the basis of expression analysis between high versus low picrosides content strains of P. kurroa so as to eliminate tissue type/ developmental variations in picrosides contents. The higher expression of the majority of the MEP pathway genes (ISPD, DXPS and ISPE), coupled with higher inhibition of DXPR enzyme by fosmidomycin, suggested that the MEP route contributed to the biosynthesis of P-I in P. kurroa. The outcome of the study is expected to be useful in designing a suitable genetic intervention strategy towards enhanced production of picrosides. Possible key genes contributing to picroside biosynthesis have been identified with potential implications in molecular breeding and metabolic engineering of P. kurroa.